Challenges and Strategies of International Students Studying in the Hainan Free Trade Port - Xu Ding; Siman Zhang; Fanying Wang; Junfeng Diao (SAGE Open)
As China’s higher education embraces internationalization, the Hainan Free Trade Port is gaining recognition as a desirable destination for international students. This study, aiming to enhance the quality of international education and to meet the diverse needs of these students in Hainan, conducted qualitative interviews with 21 international students. Employing Grounded Theory and a systematic three-tier coding process, the research revealed the students’ specific challenges within academic pursuits, social interactions, accommodations, and employment prospects. The findings informed the development of targeted recommendations designed to enhance the support framework for international students, with the broader aim of cultivating a more enriched and inclusive educational environment in Hainan.